2021
DOI: 10.1080/24740527.2021.1961081
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study of pediatric pain prevalence, assessment, and treatment at a Canadian tertiary hospital

Abstract: Background: Painful experiences are common among hospitalized children. Long-term negative biopsychosocial consequences of under-treated pain are recognized. Aims: The study benchmarks pain prevalence, assessment, and treatments as a first step to improve pain care in a Canadian tertiary hospital. Methods: Single-day audits were undertaken on the pediatric ward (PW), emergency department (ED), and maternal services (MS). Participants (child or caregiverproxy) reported hospital pain experiences in the preceding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 41 publications
0
18
0
1
Order By: Relevance
“…Unlike previous studies (Brudvik et al, 2017;Senger et al, 2021), there was high percentage of treatment of severe pain for the years studied, as well as widespread use of opioids in this context.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Unlike previous studies (Brudvik et al, 2017;Senger et al, 2021), there was high percentage of treatment of severe pain for the years studied, as well as widespread use of opioids in this context.…”
Section: Discussionmentioning
confidence: 59%
“…Despite ongoing improvements in pain relief, pediatric pain management is still insufficient worldwide(Ali et al, 2014; Farhat et al, 2013; Ferrante et al, 2013; Herd et al, 2009; MacLean et al, 2007; Williams et al, 2019). Ironically, pain induced by health professionals during various routine procedures is often underestimated, being amongst the most common sources of acute pain at the PED(Pancekauskaite and Jankauskaite, 2018; Senger et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide studies demonstrate that most hospitalized children (78%-94%) experience acute pain 8,14,29,37,38 that is often inadequately assessed and undertreated. In 2011, research involving 8 Canadian pediatric hospitals demonstrated the regular occurrence of painful procedures, yet less than one-third of these children had a documented pain intervention.…”
Section: Introductionmentioning
confidence: 99%
“…31 More recent studies from Canada, Europe, and South Africa show the continued high prevalence (24% to 63%) of moderate to severe acute pain reported in hospitalized children, commonly from needle procedures and often performed without adequate analgesic strategies. 8,29,37,40 Critically unwell neonates are particularly vulnerable to undertreated pain. A recent systematic review showed that neonates in a neonatal intensive care unit underwent up to 17 painful procedures each day, 8 most performed without pain relief.…”
Section: Introductionmentioning
confidence: 99%
“…Pain control is a fundamental human right, yet publications over the years show that hospitalized children face inadequately assessed and undertreated pain. 12,50,61,62 Painful procedures, including needles and medical and surgical conditions, such as trauma, are common. Up to 3 quarters of pediatric patients worldwide suffer moderate to severe pain, most commonly from needle procedures performed with no or inadequate analgesia.…”
Section: Introductionmentioning
confidence: 99%